Are scientists really doing science? : Personal reflections on the NIH grant system - Pollack, Gerald H. (2010)
This brief essay summarizes some personal thoughts on the NIH grant system. The thoughts arise in part from my experience as a dissenter from scientific orthodoxy, and in part from my experience as a member of several workshops convened to assess and fix problems with the NIH and NSF grant systems.